KARAKTERISTIK MENTOR PADA KEGIATAN PELATIHAN DASAR CALON PEGAWAI NEGERI SIPIL CPNS - ATPRIATNA UTAMA (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2021)
The mentoring program in basic training activities for civil servant candidates aims to improve the professionalism of civil servants at the beginning of community service. The relationship between mentors and mentees is fundamental and crucial to realizing the goals of mentors and mentees. This study aims to determine the character of the mentor's "admirable characteristics" in the actualization of basic training for civil servant candidates. This research on the phenomenon of the interpretive paradigm uses a qualitative approach with data taken from interviews using purposive sampling, observing mentor-mentee interactions, and analyzing seminar documents. The findings of this study show that, in general, mentors have ideal and professional characteristics. "Humble" characteristics and "teacher" professionalism are indicators that mentors can visualize against mentees. These are characters that are able to create connections that are able to build and develop the potential of the mentee and realize success. basic exercise. However, this positive condition is very contradictory to the condition of the results of the interview. It has been found that there are mentors who ignore their functions. So the strategies currently recommended are the availability of schedules, technical guidance, and transparency of the mentor-mentee relationship. The personality of the mentor is fundamental to the implementation of a good and effective mentoring process. ABSTRAK Program mentoring dalam kegiatan pelatihan dasar Calon Pegawai Negeri Sipil bertujuan untuk meningkatkan profesionalisme Pegawai Negeri Sipil diawal pengabdian di masyarakat, hubungan mentor dan mentee merupakan fundamental dan krusial untuk mewujudkan tujuan dari mentor dan mentee. Penelitian ini untuk mengetahui karakter mentor “Admirable Characteristics” kegiatan aktualisasi latihan dasar Calon Pegawai Negeri Sipil. Penelitian penomena paradigma interprentif ini dengan pendekatan kualitatif, data yang diambil bersumber dari interview secara pusposive sampling, observasi interkasi mentor – mentee, dan menganalisa dokumen hasil seminar. Temuan dari penelitian ini adalah bahwa secara umum mentor memiliki karakter ideal dan profesional, karakter “humble” dan profesionalisme “teacher” menjadi indikator yang mampu divisualkan mentor terhadap mentee, ini karakter yang mampu mewujudkan koneksi yang mampu membangun dan mengembangkan potensi dari mentee dan mewujudkan keberhasilan latihan dasar. Namun kondisi positif tersebut sangat kontrakdiktif dengan kondisi hasil wawancara telah ditemukan terdapat mentor yang mengabaikan fungsinya. Strategi yang direkomendasikan adalah tersedianya jadwal, petunjuk teknis dan transparansi hubungan mentor-mentee. Kepribadian mentor menjadi fundamental terselengaranya proses mentoring yang baik dan efektif.